2018
DOI: 10.29252/jafm.11.01.28357
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Analysis on Aerodynamic Behavior of a Car Model with Vortex Generators at Different Yaw Angles

Abstract: Investigating the effects of aerodynamic characteristics in the automotive segment has been one of the thrust areas of research in the recent years. Extensive research had been carried out earlier in minimizing the aerodynamic drag of the car body and to study the effects using passive air flow deflectors. Little work has been conducted on semi-active or actively controlled air flow modification techniques. In order to contribute new knowledge in the chosen area and to draw the attention of current researchers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 19 publications
0
8
0
2
Order By: Relevance
“…The effectiveness of VGs are also evaluated numerically on SUV and Ahmed body with a drag reduction of 4.2% and 10%, respectively [44]. On the other hand, an experimental and numerical investigation has been carried out on a sedan car using 3 delta type of VGs at different yaw angles [45], where the middle VG was kept stationary and remaining two were changed with their angle using smaller stepper motor as shown in Figure 15.…”
Section: Vortex Generatormentioning
confidence: 99%
“…The effectiveness of VGs are also evaluated numerically on SUV and Ahmed body with a drag reduction of 4.2% and 10%, respectively [44]. On the other hand, an experimental and numerical investigation has been carried out on a sedan car using 3 delta type of VGs at different yaw angles [45], where the middle VG was kept stationary and remaining two were changed with their angle using smaller stepper motor as shown in Figure 15.…”
Section: Vortex Generatormentioning
confidence: 99%
“…3.a. The Reynolds number (Re) for the truck model at wind speed = 30 m/s was calculated based on the equation Shankar et al 2018 shown below and the value was 1.246×10 6 which is similar to the standard critical Reynolds number.…”
Section: Coefficient Of Dragmentioning
confidence: 91%
“…VGs and riblets are smaller and are adapted to the law regulations of the practical use. Different VGs studies have been conducted through experiments and numerical simulations (Aider et al 2010;Krajnović 2014;Pujals et al 2010;Selvaraju and Parammasivam 2019;Shankar and Devaradjane 2018). The coherent and longitudinal vortex structures along the streamwise direction are generated by the influence of VGs; such vortices push high-momentum fluid to the near-wall region.…”
Section: Introductionmentioning
confidence: 99%